Caracterização clínica de crianças vítimas de trauma craniano por abuso : série de casos - 10 anos de experiência - Strang, Ana Gabriela Gomes Ferrari (2015)
Purpose: to report the characteristics of shaken baby syndrome - abusive head trauma in a regional Brazilian Children`s hospital and just comparing with international researches. Insert Brazil in the international context collaborating with our data to the fight against violence in childhood. Placing Brazil at the forefront in this important issue. Methods: 40 medical reports were reviewed. The main inclusion criterion was having tomography or magnetic resonance skull with intracranial bleeding. The data assessed were: sex, age, reason for current admission, previous admission, comorbidity, previous emergency admission, deaths, outpatient follow-up, after-effects, head computed tomography (CT scan), brain magnetic resonance (MRI), skeletal x-rays, retinal hemorrhages, head circumference measurement. Results: 11 cases of abuse head trauma (AHT), 7 boys (63,6%) and 4 girls (36,7%), the mean age was 7.6 months (range: 3-22 months). All children were taken to the health service by parents. Comorbidity was found in 3 (27%) patients (two premature and one achondroplasic). Only 1 (9%) case had drug abuse by the father. Only one family confessed AHT. The main finding was inconsistency between history, physical examination and imaging. Ophthalmologic evaluation detected in 6 patients retinal bilateral hemorrhage. Subdural hematoma at different stages ofevolution was observed in all patients. Mortality was 27% and 100% of morbidity discharged. Conclusion: Cases of AHT in this study has similar features to the international literature. Is important improve the knowledge of this subject in Brazil and stablish an action protocol, well defined, in front of suspected cases.